Surface roughness and profile dataset of Ti6Al4V textured by laser ablation and spark erosionMendeley Data - Victor Caso Moreira; Artur Fernando de Vito, Junior; Fabrizio Leonardi; Sergio Delijaicov; Rodrigo Magnabosco (Data in Brief)
The Ti6Al4V alloy is widely recognized for its extensive industrial applications, particularly in the aeronautics sector, due to its exceptional strength to-weight ratio and corrosion resistance. In this context, many industrial processes depend critically on surface area, topology, and roughness. A promising approach involves combining Ti6Al4V alloy with polymer composites, which offers significant potential for engineers to design parts that are not only high-performing but also environmentally friendly. Friction stir spot welding (FSSW) emerges as a viable technique for achieving a robust bond between the metal and polymer composite materials. However, a critical factor in this process is the surface profile of the metal, which plays a pivotal role in ensuring strong adhesion between the polymer and the titanium substrate. The data provided focus on analyzing the surface profile and roughness achieved through laser ablation, an advanced technique used for surface texturing, and explores spark erosion as an alternative method.